Towards defining the Christian development organisation - Hancox, Deborah M. (HTS teologiese studies, 2019)
Around the world, there exist many organisations who claim a Christian motivation and whose work falls within the scope of the development sector. These organisations are distinctly different from local congregations, and whilst development as a field of theological study is becoming increasingly well-defined and established, there has been limited theological research and reflection on these organisations. Much about them remains unstudied and unclear, raising questions about their purpose, legitimacy and theological contribution. This in turn hampers a responsive and responsible engagement with them within the academy. Contributing to this oversight is the absence of an appropriate, commonly shared name and definition around which research and discourse can occur. This article reviews names and definitions currently being used and then proposes the name ‘Christian developmental organisation’ (CDO). It provides a rich definition, considering the CDO’s organisational, societal, purpose, activity and faith dimensions. In addition, the history dimension brings an understanding of the origins and formation of the CDO whilst the relationship dimension positions the CDO within a web of relational dynamics. It is hoped that the name and definition offered in this article will promote research and engagement with the CDO as well as aid their self-understanding.